Purification and Identification of miRNA Target Sites in Genome Using DNA Affinity Precipitation - Xun, Yu; Tang, Yingxin; Hu, Linmin; Xiao, Hui; Long, Shengwen; Gong, Mengting; Wei, Chenxi; Wei, Ke; Xiang, Shuanglin (Frontiers in Genetics, 2019)
Combination with genomic DNA is one of important way for miRNAs to perform biological processes. However, because of lacking experimental method, the identified genomic sites targeted by microRNA were only located in promoter and enhancer regions. In this study, based on affinity purification of labeled biotin at the 3’-end of miRNAs, we established an efficiently experimental method to screen miRNA-binding sequences in the whole genomic regions in vivo. Biotinylated miR-373 was used to test our approach in MCF-7 cells, and then Sanger and next generation sequencing were used to screen miR-373 binding sequences. Our results demonstrated the genomic fragments precipitated by miR-373 were not only located in promoter, but also in intron, exon and intergentic region. 11 potentially miR-373-targeting genes were selected to do further study and all of these genes were significantly regulated by miR-373. Furthermore, the targeting sequences located in E-cadherin, CSDC2 and PDE4D genes could interact with miR-373 in MCF-7 cells rather than Hela cells, which is consistent with our data that these three genes can be regulated by miR-373 in MCF-7 cells while not in HeLa cells. Above all, this is an efficient method to identify miRNAs- targeting sequences in the whole genome.